Trends in Gender Education Development at Higher School of the Post-Soviet Central Asian Countries (Journal of Educational Sciences, 2018)
This article identifies the leading development trends of gender education at higher school of thepost-Soviet Central Asian countries. Ones relate, firstly, to the legal and regulatory framework for theimplementation of gender ideas at higher education (the improvement of the legal and regulatory frameworkthat based on the gender equality principles for the system of higher education; the creation of speciallegislative and legal framework that defines the state gender policy directions in the field of gendereducation). Secondly, trends are related to the conditions for organizing gender training at the universitiesof Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, Uzbekistan (substantial similarity of featuresand peculiarities in the organization of gender education formation at higher school of the post-Sovietcountries in the Central Asian region and the uneven dynamics of its development). Thirdly, trends aremanifested in scientific activity on gender studies (legitimation of gender studies as an independentdirection in academic science of higher education and consolidation of scholars and teachers of CentralAsian countries on gender issues). Common features and peculiarities of gender education implementation are determined. Along with the positive, negative trends and their common manifestations in thepost-Soviet Central Asian countries has been established.Key words: gender equality, gender studies, gender courses, post-Soviet countries, Central Asianregion, higher education.